Work–Life Balance Academic and Psychological Well-being of Law Study Program Students - Gracia Anastasya; Rini Jesia; Juanda Badenggan (International Journal of Psychology and Health Science, 2026)
Law students face high academic demands, such as a heavy reading load of legal literature, complex case analysis, and the pressure of intensive academic evaluations. These conditions have the potential to cause academic stress and disrupt the balance between academic demands and personal life or academic work–life balance (WLB), which can subsequently impact students' psychological well-being. This study aims to determine the relationship between academic work–life balance and psychological well-being in Law students. The study used a quantitative approach with a correlational design. The study sample consisted of Law students selected using a simple random sampling technique. Data were collected through a Likert scale questionnaire that measured academic work–life balance based on the concepts of Fisher, Bulger, and Smith and psychological well-being based on Ryff's Psychological Well-Being Scale. Data analysis was performed using Pearson Product Moment correlation after meeting the assumptions of normality and linearity. The results showed a positive and significant relationship between academic work–life balance and students' psychological well-being (r = 0.678; p < 0.05). These findings suggest that students who are able to balance academic demands with personal and social life tend to have better psychological well-being. This study emphasizes the importance of managing academic work–life balance as a supporting factor for the psychological well-being of Law Study Program students.